ИНТЕНСИФИКАЦИЯ ДЕГРАДАЦИИ НЕФТЯНЫХ УГЛЕВОДОРОДОВ С ИСПОЛЬЗОВАНИЕМ МОНОКУЛЬТУР И КОНСОРЦИУМОВ МИКРООРГАНИЗМОВ-НЕФТЕДЕСТРУКТОРОВ (Experimental biology, 2009)
The paper presents data on the study of hydrocarbon activity monocultures and consortia of microorganisms-oil destructors on native soil deposits Zhanatalap under laboratory conditions. The greatest oil destructor activity noted when introducing a consortium of four strains of hydrocarbonmicroorganism.
Keywords: hydrocarbon activity monocultures